INNOVATIVE EDUCATIONAL ACTIVITY IN HIGHER EDUCATION IN THE CONDITIONS OF MODERN REFORMING OF UKRAINIAN EDUCATIONAL SYSTEM - Kuchynska, Iryna; Blashkova, Olena; Rodiuk, Nataliia; Holiuk, Oksana; Polishchuk, Svitlana; Ivanytska, Nina; Mnyshenko, Kateryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The processes of creation, development and application of innovations are increasingly spreading in the education system and pedagogical science. The specific historical situation in Ukraine necessitates the restructuring of education, its reforming and approximation to European and world standards. The aim of the study is to study the purposeful impact of these processes on the constant formation and renewal of Ukrainian pedagogical theory and practice with further rethinking the importance of innovation to increase the rating of higher educationinstitution and increasing its competitiveness.Basic research methods are surveys, observation and statistical analysis.The article emphasizes the key values of improving the modern sphere of education, pays attention to the innovative processes that take place in the modern school, and pedagogy, in particular. The peculiarities of the introduction of innovative education in higher education institutions are highlighted. The authors analyze the importance of the application and management of innovative educational processes that can help to increase the level of quality education for the success and competitiveness of higher education institution.The author's team studied the structure and dynamics of the development of educational innovation processes of modern higher education institutions, as well as the scheme of division of the innovation process, which was called the "life cycle of innovation". The importance of developing individual perception of a particular applicant of the proposed innovations during studying at the higher education institution is proved.It is noted that it is important to develop the initiative of teachers of Ukrainian higher education institutions before making decision about necessity to introduce innovations of a certain type.